EVALUATION OF HERMETIC STORAGE BAGS FOR THE MANAGEMENT OF PULSE BEETLE, Callosobruchus maculatus (FAB.) IN CHICKPEA - P. Chaithanya (The Journal of Research ANGRAU, 2024)
Studies on management of pulse bruchid, Callosobruchus maculatus (Fab.) on stored chickpea (Cicer arietinum L.) through hermetic storage was carried out in the laboratory of Department of Entomology, Agricultural College, Bapatla during 2021-22.Three hermetic storage bags viz., super bag, polythene bag and triple layer plastic bag were evaluated along with conventional storage bags against pulse beetle damage and seed quality parameters of stored chickpea for six months storage period. Chickpea grains stored in super bags recorded zero number of adult beetles of C. maculatus, zero grain damage, no moisture change, and above 90 percent viability of chickpea grains upto six months storage period followed by triple layer plastic bags and found to be the most effective when compared to other types of bags tested.